Integrative analyses of morpho-physiological, biochemical, and transcriptomic reveal the seedling growth response of Pinus yunnanensis to nitrogen and phosphorus fertilization - Xu, Junfei; Li, Xiyan; Chen, Shi; Chen, Lin; Tang, Junrong; Chen, Peizhen; Cai, Nianhui; Xu, Yulan (Frontiers in Plant Science, 2025)
Appropriate nitrogen (N) and phosphorus (P) fertilization is critical for plant growth and production. Pinus yunnanensis, a silvicultural tree in southwestern China, faces economic and ecological limitations due to nutrient deficiency in the soils in its distribution areas. The slow growth of this species during the seedling stage exacerbates these problems. Therefore, it is important to realize the regulating effects of N and P proportioning fertilization on seedling growth to enhance nutrient-use efficiency. In this study, variations in morphological, physiological, and biochemical characteristics of seedlings were analyzed under nine treatments of NP proportioning in an open nursery using a regression design. Growth in height and basal diameter increased and showed an approximate tendency in all treatments. The maximum biomass accumulation was observed at 480 d after treatment in roots of T5 (14.714 g) (application N 0.4 g·per−1 and P 3 g·per−1), stems of T5 (12.654 g), leaves of T9 (24.261 g) (application N 0.8 g·per−1 and P 6 g·per−1), aboveground parts of T9 (35.402 g) and individuals of T5 (49 g). The total chlorophyll content peaked in the leaves at 120 d and was correlated with the peak levels of N, P, and K in leaves. The content and reserves of nutrient elements in the organs of seedlings subjected to NP proportioning were significantly higher than those in unfertilized seedlings. Analysis of nutrient utilization efficiency revealed that T5 demonstrated superior seedling growth performance. Appropriate fertilization dosage of N and P for P. yunnanensis seedlings in this study was 0.32 g·per−1–0.58 g·per−1 and 3.02 g·per−1–4.95 g·per−1 respectively, using path analysis and regression equation. Transcriptomic sequencing revealed that there were 2,301 DEGs between T5 and T1 (control), which were involved in the uptake and assimilation of nutrients, biosynthesis of phytohormones and secondary metabolites, and photosynthesis. Additionally, the abundance of genes involved in cell division and proliferation, cellulose biosynthesis, and cell wall extension were dramatically upregulated, which potentially correlated with enhanced seedling growth. In conclusion, this study provides comprehensive information on the response of seedlings to varying proportions of N and P and may promote the growth of P. yunnanensis seedlings by optimizing the proportion of N and P in fertilizers.